A dual based on the oxidase mimicking activity of MnO.sub.2 nanosheets - Ma, Zhangyan; Wu, Tengteng; Li, Peipei; Liu, Meiling; Huang, Si; Li, Haitao; Zhang, Youyu (Mikrochimica acta (1966), 2019)
A fluorimetric and colorimetric method is described for the determination of glutathione (GSH) and silver (I). It is based on the use of MnO.sub.2 nanosheets that were prepared by solution mixing and exfoliation. They display oxidase-mimicking activity and can catalyze the oxidation of o-phenylenediamine (OPD) to form yellow 2,3-diaminophenazine (DAP) with an absorption maximum at 410 nm. DAP also has a yellow fluorescence (with a peak at 560 nm). The MnO.sub.2 nanosheets can be rapidly reduced to Mn.sup.2+ by GSH. This reduces the efficiency of the oxidase mimic MnO.sub.2 and causes a decrease in fluorescence and absorbance intensity. However, on addition of Ag.sup.+, a complex is formed with GSH. It prevents the destruction of MnO.sub.2 nanosheets so that the enzyme mimicking activity is retained. A dual-method for the determination of GSH and Ag(I) was developed. It has excellent sensitivity for GSH with lower detection limits of 62 nM (fluorimetric) and 0.94 [mu]M (colorimetric). The respective data for Ag(I) are 70 nM and 1.15 [mu]M. The assay was successfully applied to the determination of GSH and Ag(I) in spiked serum samples.